Правове регулювання виробничої практики лікарських засобів передової терапії у контексті змін сучасного законодавства України - Андрійчук, Б. І.; Самчук-Колодяжна, З. Ф. (НДІ ПЗІР НАПрН України, 2022)
Наближення українського законодавства до законодавчої бази Європейського Союзу дозволяє вдосконалювати системи забезпечення виробництва інноваційних лікарських засобів, зокрема лікарських засобів передової терапії. Це у свою чергу потребує належно оновленої законодавчої бази, яка має відповідати європейським стандартам. Прийняття настанови СТ-Н МОЗУ 42-4.0:2020 в Україні знаменувало собою новий етап регулювання виробничої практики лікарських засобів передової терапії. Однак, ефективність реалізації положень даного документу на пряму залежить від рівня узгодженості вітчизняних стандартів виробничої практики даної категорії лікарських засобів із стандартами Європейського Союзу. Саме тому постає необхідність здійснення аналізу сучасного стану вітчизняної системи нормативно-правового регулювання у сфері виробничої практики лікарських засобів передової терапії. Загальна характеристика нормативно-правового регулювання суспільних відносин, які складаються у сфері виробничої практики лікарських засобів ставали предметом розгляду таких вчених правників як: О. Г. Алексєєв, О. Я. Андрійчук, С. В. Васильєв, В. М. Пашкова та інші. Однак, в сучасній юридичній літературі та у працях даних науковців зокрема, не піднімалися питання, пов’язані з виробничою практикою лікарських засобів передової терапії для використання людиною. Метою даного дослідження є аналіз українського законодавства та законодавства ЄС, що регулює виробничу практику лікарських засобів прогресивної терапії. В ході розвитку правового визначення ATMP змінювали назву від «високотехнологічні (біотехнологічні) лікарські засоби» на «лікарські засоби передової терапії». Виробнича практика останніх уперше була врегульована СТ-Н МОЗУ 42-4.0:2013, що був прийнятий на основі Додатку 2 Тому 4 EudraLex 2013 року. Згодом у зв’язку з прийняттям європейської настанови щодо GMP для ATMP у 2018 році була створена в Україні настанова СТ-Н МОЗУ 42-4.9:2020 як частина СТ-Н МОЗУ 42-4.0:2020. У СТ-Н МОЗУ 42-4.9:2020 вперше згадано комбіновані лікарські засоби для передової терапії (комбіновані ATMP) як окрему підгрупу ATMP, передбачені окремі заходи для виробництва комбінованих ATMP, а також надано вичерпний перелік усіх інших видів ATMP, що відповідає положенням Регламенту (ЄС) № 1394/2007. Попри те, що вітчизняна настанова є належним чином гармонізована з європейськими стандартами у відповідній сфері виробництва є необхідність прийняття допоміжних нормативних актів, покликаних на реалізацію окремих положень СТ-Н МОЗУ 42-4.0:2020. Problem setting. The approximation of Ukrainian legislation to the European Union (EU) legislative framework allows for the improvement of systems for the production of innovative medicinal products, particularly advanced therapy medicinal products (ATMP). This, in turn, requires a properly updated legislative framework that must meet EU standards. The adoption of the guideline of the Ministry of Health of Ukraine 42-4.0:2020 marked a new stage in the regulation of the production practice of ATMP in Ukraine. However, the effectiveness of implementing the provisions of this Ukrainian guideline directly depends on the level of consistency of the domestic standards of ATMP manufacturing practice with the standards of the European Union. That is why analysis is necessary to be carried out to define the current state of the Ukrainian system of legal regulation in the field of manufacturing practice of ATMP. Analysis of recent researches and publications. The general characteristics of legal regulation of public relations, which are formed in the manufacturing practice of medicinal products, became the subject of consideration by such researchers as O. G. Alekseev, O. Ya. Andriichuk, S.V. Vasiliev, V. M. Pashkova and others. However, in modern legal literature, issues related to the manufacturing practice of ATMP for human use were not raised. The target of the research is to analyse of Ukrainian and EU legislation regulating the manufacturing practice of ATMP. A rticle’s main body. The regulation of ATMP production within the framework of the European legislative process was directly related to all four categories of the latter, which was finally defined and fixed by the adoption of Regulation 1394/2007/EC of the European Parliament and of the Council, which entered into force on December 30, 2008. Since that time, active work had begun on the introduction of a new category of biological medicinal products (such as ATMP) to Volume 4 of EudraLex, which ended with the implementation on January 31, 2013, of the amended Appendix 2 of Volume 4 of EudraLex, which contained, along with the general rules for implementing good manufacturing practices of medicinal products as well as special regulations related to the manufacturing of ATMP. Subsequently, in connection with the update of manufacturing practice standards and as a result of the adoption of the guidelines on Good Manufacturing Practice specific to Advanced Therapy Medicinal Products (European guideline on GMP for ATMP) in 2018, the provisions of Annex 2 Therefore 4 of EudraLex were changed and no longer applied on ATMP. Following the development of the legal definition of ATMP in Ukrainian legislation, we should note that in the guideline of the Ministry of Health of Ukraine 42-4.0:2013, in contrast to the previous editions, such a category of medicinal products as «high-technology (biotechnological) medicinal products» was used for the first time. The Ukrainian implementation of the European guideline on GMP for ATMP was carried out in 2020. The guideline of the Ministry of Health of Ukraine 42-4.0:2020 was created with a separate guideline 42-4.9:2020 as a part of it. The ATMP was used instead of «high-technology (biotechnological) medicinal products» in the guideline 42-4.9:2020. Conclusions and prospects for the development. During the development of the legal definition of ATMP in Ukrainian legislation, the term was changed from «high-tech (biotechnological) medicinal products» to «advanced therapy medicinal products». The manufacturing practice of the ATMP was first regulated by the guideline of the Ministry of Health of Ukraine 42-4.0:2013, which was based on Appendix 2 Volume 4 of EudraLex in 2013. Then, due to the adoption of the European guideline on GMP for ATMP in 2018, the next Ukrainian guideline was created in Ukraine, namely 42-4.9:2020 as part of the guideline of the Ministry of Health of Ukraine 42-4.0:2020. The guideline 42-4.9:2020 for the first time introduced combined ATMPs as a separate subgroup of ATMP, provided separate measures for the production of combined ATMPs, and also indicated an exhaustive list of all other types of ATMPs that comply with the provisions of Regulation 1394/2007/EC of the European Parliament and of the Council. Although the domestic guidelines are properly harmonized with European standards of ATMP manufacturing, there is a need to adopt auxiliary normative acts designed to implement certain provisions of the guideline of the Ministry of Health of Ukraine 42-4.0:2020.
Keywords: лікарські засоби передової терапії; виробнича практика; лікарські засоби; EudraLex; гармонізація; імплементація; advanced therapy medicinal products; manufacturing practice; medicinal products; EudraLex; harmonization; implementation; standards